489 A COMPREHENSIVE ANALYSIS OF ANASTOMOTIC COMPLICATIONS FOLLOWING ESOPHAGECTOMY. (14th September 2020) - Katz, A; Bendayan, S; Hilzenrat, R; L Ramirez-GarciaLuna, J; Kammili, A; Al Lawati, Y; Abureida, F; Nevo, Y; Cools-Lartigue, J; Spicer, J; Mueller, C; Ferri, L
Abstract:  : Post-esophagectomy anastomotic complications can result in high morbidity/mortality. Those with necrosis and sepsis have traditionally resulted in conduit loss and cervical esophagostomy. We sought to examine our management and outcomes of anastomotic complications, with a focus on an approach that stresses conduit salvage. Methods: Conduit complications were identified from a prospectively collected esophagectomy database (2006–17) at a high-volume referral center. Patient/tumor/treatment details and surgical outcomes were collected. Conduit complications were defined as Leak/Conduit Necrosis/Tracheoesophageal Fistula (TEF) and graded according to the Clavien-Dindo classification. Successful treatment was defined when sepsis/leak control was achieved and no further intervention was required. Statistical analysis was done using Cox regression, logistic regression, ANOVA or Chi-square tests, *p < 0.05. Results: Of 647 esophagectomies, conduit complications occurred in 103 (16%) [Leak:73 (11%); Necrosis:24 (4%), (TEF):6(1%)]. Antibiotics (C-D = 2) was successful in 28 (38%) of Leaks. Endoscopic stent alone (C-D = 3A) was successful in 20 (27%) Leak, 7(29%) Necrosis, and 1(17%) TEF cases. Early conduit revision+re-anastomosis (C-D = 3B/4) was successfully performed in 22 (30%) Leak, 13 (54%) Necrosis, and 5(83%) TEF cases. Only 6 patients [2(3%) Leak, 4(16%) Necrosis] had conduit loss+cervical esophagostomy. 90-day mortality was: Minor (C-D = 2-3A) Leak = 3%, Major (C-D = 3B-4) Leak = 8%, and Necrosis = 21%*. Necrosis, but not Leak or TEF, was associated with lower 3-year survival compared to patients who did not have conduit complication (30% vs 55%, p < 0.008). Conclusion: The vast majority of conduit complications, including conduit necrosis, can be managed successfully with conduit salvage with endoscopic treatment or early surgical re-anastomosis. Cervical esophagostomy is rarely required.